Elevated Circulating Interleukin-27 in Patients with Coronary Artery Disease Is Associated with Dendritic Cells, Oxidized Low-Density Lipoprotein, and Severity of Coronary Artery Stenosis. (13th July 2012) - Jin, Wen; Zhao, Yiqiao; Yan, Wen; Cao, Longxing; Zhang, Weiwei; Wang, Ming; Zhang, Ting; Fu, Qiang; Li, Zhiliang
Abstract : Coronary artery disease (CAD) is an immune-mediated chronic inflammatory disease mainly caused by atherosclerosis. The aims of this study were to investigate the role of interleukin-27 (IL-27) in patients with CAD and the severity of coronary artery lesions, which was evaluated by Gensini score and to investigate the biosynthesis of IL-27 and oxidized low-density lipoprotein (ox-LDL) in vitro using monocyte-derived dendritic cells (DCs). To this aim, plasma levels of IL-27, ox-LDL, and Gensini score were analyzed in patients with CAD (n = 136 ) and normal subjects (controls, n = 29 ). IL-27 concentration of the supernatant and the mRNA expression levels of p28 and ebi3, subunits of IL-27, from cultured immature DCs incubated with different concentrations of ox-LDL for 24 h were also analyzed. We found that circulating IL-27 levels were significantly elevated in patients with CAD than in controls (P < 0.01 ), and positively correlated to ox-LDL and Gensini score. ox-LDL dose-dependently upregulated expression of both IL-27 protein and IL-27 (p28 and EBI3) mRNA in vitro, indicating that ox-LDL can stimulate DCs to produce IL-27. These results demonstrate that IL-27 might regulate the network of immunity and inflammation in the pathogenesis of atherosclerosis.